PHARMACOLOGICAL EFFECTS ON THE CENTRAL NERVOUS SYSTEM INDUCED BY COUMARIN, ISOLATED FROM Hygrophila tyttha LEONARD - ARIZA, Sandra Y.; RUEDA, Diana C.; RINCÓN V., Javier; LINARES, Edgar L.; GUERRERO, Mario F. (Vitae, 2009)
This study shows the isolation, identification and pharmacological profile on the central nervous system induced by coumarin (1-2 benzpyrone), molecule obtained from Hygrophila tyttha Leonard (Acanthaceae. Vulgar name:: “amansamachos”). This specie is a medicinal plant used in Colombian traditional medicine for the treatment of anxiety. Tests destined to detect possible activity of anxiolytic type (elevated plus maze, marble burying behavior), anticonvulsant (electroshock, pentylenetetrazole), sedative (pentobarbital and ether sleep time) and miorelaxant (wiring test) were used in albino ICR mice. According to the positive results in the plus maze, marble burying, electroshock and sleep tests, coumarin (200 mg/kg, po) seems to be a key compound in the pharmacological response induced by Hygrophila tyttha. These results may led to the finding of therapeutic alternatives of anxiolytic, anticonvulsant and/or sedative kind from this natural compound.